Studi Prencanaan Pembangkit Listrik Tenaga Mikro Hidro Di Danau Andeman, Desa Sanankerto Kecamatan Turen, Kabupaten Malang - Dermawan, Very -; Augustiman, Yoggie Azhary (Jurnal Mahasiswa Jurusan Teknik Pengairan, 2018)
Danau Andeman merupakan tempat wisata yang terletak di Desa Sanankerto Kecamatan Turen Kabupaten Malang. Desa Sanankerto memiliki tujuan menjadi desa wisata. Namun, saat ini tempat wisata masih kurang dikenal oleh banyak orang, penerangan pada malam hari di tempat wisata tersebut seadanya karena memperhitungan biaya ekonomi. Danau Andeman yang menjadi aset penting Desa Sanankerto, dengan pemanfaatan hanya untuk kebutuhan air bersih rumah tangga, dan irigasi di Desa Sanankerto. Wisata pada desa tersebut akan beroperasi di malam hari. Dengan dibangunnya PLTMH, maka diharapkan listrik yang dihasilkan oleh PLTMH dapat menambah pemenuhan kebutuhan listrik di tempat wisata tersebut, sehingga menjadi lebih baik penerangannya dan semakin menarik minat wisatawan. Debit yang diketahui di danau andeman yaitu sebesar 0.37 m3/det yang diperoleh dari pengukuran di lapangan selama 7 hari dengan pengukuran tiap jam dari jam 09.00 – 16.00 dengan 3 lokasi pengukuran. Pemilihan turbin melihat dengan kondisi di lapangan dan mana yang lebih efisien dari segi bangunan sipil yang digunakan maka dipilih turbin whirlpool. Pada perencanaan PLTMH Desa Sanankerto mempunyai dua alternatif yang membedakan hanya jumlah turbin yang direncanakan, daya listrik pertahunnya yang dihasilkan pada alternatif satu sebesar 88072.47 kWH dengan anggaran biaya sebesar Rp. 1.096.833.252 dengan nilai BCR = 0.40; NPV = -Rp. 1.116.242.437,28; dan IRR = -0.0754% pada alternatif dua daya listrik pertahunnya yang dihasilkan sebesar 78146.90 kWH dengan anggaran biaya sebesar Rp. 797.853.083 dengan nilai BCR = 0.49; NPV = -Rp.692.771.953,14; dan IRR =      -0.0519%. Kata Kunci: PLTMH, Pengukuran Debit, Turbin Whirlpool, Daya Listrik, Kelayakan EkonomiAndeman Lake is a tourism object that is located in Sanankerto Village, Turen District, Malang Regency. Being a tourism object is a goal of the village. However, it still don't get enough attention from the tourist since the lighting at night  at the tourism object is inadequate and it needs additional cost to improve the lighting. Andeman Lake is an important asset of Sanankerto Village, with utilization only for households clean water needs, and irrigation in Sanankerto Village. Tourism in the village will operate at night. With the construction of MHPP, it is expected that the electricity generated by MHPP can increase the fulfillment of electricity needs in the tourist attractions, so that the better lighting and increasingly attract tourists. Known discharge in lake andeman is 0.37 m3/ s obtained from field measurements for 7 days with hourly measurements from 09.00 - 16.00 hours with 3 measurement locations. The turbine selection to see with the conditions in the field and which is more efficient in terms of civil structure used then selected  whirlpool turbine. In the MHPP planning of Sanankerto Village has two alternatives which distinguished from the number of planned turbines, annual electric power generated in the first alternative amounted  88072.47 kWH with a budget cost of Rp. 1.096.833.252 with the value of BCR = 0.40; NPV = -Rp. 1.116.242.437,28; and IRR = -0.0754%  in the annual electric power generated amounted 78146.90 kWH with a budget cost of Rp. 797.853.083 with the value of BCR = 0.49; NPV = -Rp. 692.771.953,14; and IRR = -0.0519%.Andeman Lake is a tourism object that is located in Sanankerto Village, Turen District, Malang Regency. Being a tourism object is a goal of the village. However, it still don't get enough attention from the tourist since the lighting at night  at the tourism object is inadequate and it needs additional cost to improve the lighting. Andeman Lake is an important asset of Sanankerto Village, with utilization only for households clean water needs, and irrigation in Sanankerto Village. Tourism in the village will operate at night. With the construction of MHPP, it is expected that the electricity generated by MHPP can increase the fulfillment of electricity needs in the tourist attractions, so that the better lighting and increasingly attract tourists. Known discharge in lake andeman is 0.37 m3/ s obtained from field measurements for 7 days with hourly measurements from 09.00 - 16.00 hours with 3 measurement locations. The turbine selection to see with the conditions in the field and which is more efficient in terms of civil structure used then selected  whirlpool turbine. In the MHPP planning of Sanankerto Village has two alternatives which distinguished from the number of planned turbines, annual electric power generated in the first alternative amounted  88072.47 kWH with a budget cost of Rp. 1.096.833.252 with the value of BCR = 0.40; NPV = -Rp. 1.116.242.437,28; and IRR = -0.0754%  in the annual electric power generated amounted 78146.90 kWH with a budget cost of Rp. 797.853.083 with the value of BCR = 0.49; NPV = -Rp. 692.771.953,14; and IRR = -0.0519%.  Keywords: MHPP, discharge Measurement, Whirlpool Turbine, Electric Power, Economic Feasibility